Predictors of seasonal influenza vaccination in chronic asthma - Asciak, Rachelle; Balzan, Martin; Buttigieg, Jesmar (Multidisciplinary Respiratory Medicine, 2013)
Background: Guidelines advise annual influenza vaccination in chronic asthma. The aim of this study was to determine uptake of the influenza vaccine in a group of patients (n = 146) with moderate to severe chronic asthma and establish the main predictors of vaccination. Method: Patients attending a hospital asthma clinic were asked to complete a questionnaire in February 2012 (n = 146). These same patients were contacted a year later via telephone (n = 109 responded), and they were asked to complete the same questionnaire. Results: Vaccination rate was 50.3% in winter 2011/12, and 57.8% in 2012/13. Using binary logistic regression, the predictors for vaccination in 2012 were patient advice (Odds ratio [OR] 15.37 p = 0.001), female gender (OR 2.75, p = 0.028), past side effects (OR 0.21, p = 0.001) and comorbidity (OR 0.39, p = 0.013). Stepwise regression resulted in age as predictor (T value = 3.99, p = 0.001). On analyzing the responses from the second questionnaire at one year after attendance to asthma clinic, predictors changed to compliance to medication (OR 9.52, p= 0.001) and previous exacerbations (OR 4.19, p = 0.026). Out of the 56 patients vaccinated in 2011/12, 33 reported asthma exacerbations before 2012, and 29 reported asthma exacerbations after receiving the influenza vaccine. Out of the 46 unvaccinated patients in 2012, 27 had asthma exacerbations before 2012 and 19 patients had exacerbations in 2013. Patients vaccinated in 2011/12 needed 0.59 courses of steroid/patient/year, and 1.23 visits for nebulizer/ patient/year while non-vaccinated patients needed 0.18 courses of steroids/patient/year (p = 0.048), and 0.65 visits for nebulized/patient/year (p = 0.012). Patients’ subjective statements broadly confirmed the predictors. 16/69 (23.1%) received the vaccine in winter 2012/13 despite reporting previous side effects. Conclusions: Advice to patient, female gender and patients’ age predicted vaccination, while past side effects to the influenza vaccine, and presence of comorbidities predicted non vaccination. Symptomatic asthma patients are more likely to be vaccinated. One year after the first contact, treatment compliance and previous asthma exacerbations gained statistical significance as predictors of vaccination.